The Effect of Young Papaya Seed Extract on The Motility and Abnormality of Male Mice Spermatozoes (Mus musculus) - Tannya Efritzka Louise Calame; Kusmiyati Kusmiyati; I Wayan Merta (Jurnal Pijar Mipa, 2021)
Papaya fruit has many benefits, one of which is papaya seed can be used as antifertility drugs, especially young papaya seeds. Young papaya seeds contain secondary metabolites of alkaloid glycosides and proteolytic enzymes such as papain which can interfere with spermatogenesis. The study aims to determine the effect of young papaya seed extract on the sperm motility and abnormality of male mice (Mus musculus). Mice were randomly selected to represent 4 dose groups: control group (P0), extract 30mg/grBW (PI), extract 60mg/grBW (PII) and extract 90mg/grBW (PIII). Each treatment group was carried out with six repetitions. The treatment was given intravenously by injecting it in the tail of the mice for 15 consecutive days. The observed spermatozoa quality variables included a percentage of motile sperm and abnormal sperm. Data analysis using one-way ANOVA test with a significance level of 5% (0,000) and continued with the LSD (Least Significant Difference) with a 95% confidence level. The study on the Quality of spermatozoic showed a significant effect at the doses of 60mg/grBW (PII) and 90mg/grBW (PIII). The higher dose of young papaya seed extract increasingly affects the Quality of sperm. This research concluded that the extract of young papaya seeds has a significant impact on mice spermatozoa (Mus musculus) quality.